Aerobic physical exercise improves quality of life in temporal lobe epilepsy - Laks, Shai Oisiovici; Volpato, Nathalia; Coelho, Nikolas; Nogueira, Mateus Henrique; Henning, Pamela Regina; Dias, Aline de Fatima; Ferreira, William Souza Martins; Yasuda, Clarissa Lin; Pimentel-Silva, Luciana Ramalho; Cendes, Fernando (Arquivos de Neuro-Psiquiatria, 2025)
Background A prior study showed that people with temporal lobe epilepsy (TLE) with an active lifestyle present a better quality of life (QoL), but the influence of aerobic physical exercise (APE) in the QoL of these patients is still unclear. As pharmacoresistance is commonly associated with TLE, the possibility of seizures during the activities might prevent patients from benefiting from APE.Objective To analyze the influence of APE in the QoL of TLE patients and also focus on the seizure worry subitem of the QoL in epilepsy 31 (QoLIE-31) questionnaire.Methods We analyzed data from 25 individuals with TLE who participated in a 6-month APE program under the supervision of a board-certified physical trainer. TLE patients were divided into training (TLE-training) and control (TLE-control) groups. The TLE-training group underwent an APE program of 6 months, while the control group was oriented to keep their routine. We assessed all patients with the QoLIE-31 at baseline and after 6 months. We used a mixed-between-subjects ANOVA to assess the APE intervention compared with TLE-control pre- and postintervention on the QoL.Results We found a significant interaction between intervention groups and APE-time (p = 0.0005), showing that only patients in the TLE-training group presented higher QoL after the intervention (p = 0.001). We found no significant differences between groups for seizure worry (p = 0.50).Conclusion There was improvement in QoL due to APE, with no increase in seizure worry, which might be a feature of concern for both patients and healthcare practitioners. Further studies should focus on long-term interventions to evaluate the impact of APE in QoL.
Keywords: Epilepsy, Temporal Lobe; Quality of Life; Exercise; Seizure